(1-Oxo-2,6,7-trioxa-1-phosphabicyclo[2.2.2]octan-4-yl)methyl 4-methylbenzenesulfonate - Hou, Xu-Feng (International Union of Crystallography, 2012)
In the title compound, C(12)H(15)O(7)PS, the P atom has a distorted tetrahedral environment. The P—O—C—C torsion angles deviate significantly from zero [average = 12.0 (3)°], indicating that the bicyclic OP(OCH(2))(3)C cage is strained. In the crystal, weak C—H⋯O interactions consolidate the packing.